Birds of the Indian Subcontinent : India, Pakistan, Sri Lanka, Nepal, Bhutan, Bangladesh and the Maldives. - Grimmett, Richard (Helm field guides., 2012)
This new field guide covers all the bird species found in India, Pakistian, Sri Lanka, Nepal, Bhutan, Bangladesh and the Maldives.